3 Disrupted avoidance learning in functional neurological disorder. Issue 8 (13th July 2017) - To, Benjaman; Morris, Laurel S; Baek, Kwangyeol; Chang-Webb, Yee-Chien; Mitchell, Simon; Strelchuk, Daniela; Mitchell, Simon; Strelchuk, Daniela; Mikheenko, Yevheniia; Phillips, Wendy; Zandi, Michael; Jenaway, Allison; et al.
Abstract : Objective: Functional neurological disorder (FND) is characterised by unexplained neurological symptoms, including movement, seizures or sensory symptoms that are unrelated to an underlying neurological disorder. As FND presents as ∼16% cases in neurology clinics (Stone et al, 2010) and the current understanding of its aetiology is limited, research into the neural disturbances present in this group is critical. FND subjects have been shown to display enhanced amygdala activity to arousing stimuli (Voon et al, 2010), however delineation of the roles of each subnuclei have not yet been achieved. In this study, we examined the response of FND subjects to fear conditioning and their sensitivity to loss. Method: 25 FND and 20 healthy volunteers (HV) were conditioned to aversive/negative affective (CS+) or neutral (CS-) stimuli. During functional MRI, subjects performed a two-choice learning task to avoid monetary loss. The stimuli used in the two-choice task included the previously conditioned stimuli and were associated with a greater likelihood of a loss outcome. Results: FND patients were more impaired at learning to avoid losses. Using reinforcement learning modelling, we show that FND subjects had a more negative valuation of the CS+ and greater noisy choice behaviours in the context of the CS+. Compared to HV, FND patients showed enhanced Centromedial amygdala responses to loss compared to neutral feedback in the context of the negative/aversive CS+, which correlated with greater impairments in avoidance learning. Conclusion: The findings show that although FND patients have enhanced sensitivity to negative outcomes, this fails to be adaptive, and is not used to guide avoidance learning. We show no evidence for greater harm avoidance but rather a generalised impairment in the capacity to use negative outcomes to guide behaviours. Furthermore, fearful learned contexts enhance the randomness of choice behaviours, thus highlighting a potential mechanism by which negative contexts interfere with adaptive behaviours. Our findings further detail the aetiology of a common but elusive disorder and highlight the potential utility of interventions targeting the salience of negative stimuli.